Molybdenum nitride / nickel-cobalt nitride nanosheet heterostructure electro-catalytic material as well as preparation method and application thereof
By growing copper nanowires on foam copper and synthesizing molybdenum nitride and nickel cobalt nitride nanosheets to form a molybdenum-doped nickel cobalt nanosheet covering structure, the problems of high cost, insufficient stability and limited activity of platinum-based catalysts are solved. It achieves high-efficiency and low-cost hydrogen evolution performance of high current density.
Patent Information
- Application Number
- CN202411867443.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing platinum-based catalysts have problems such as high production costs, insufficient stability and limited activity in fuel cells, making it difficult to maintain high-efficiency performance under high current density.
Molybdenum nitride/nickel cobalt nitride nanosheets heterostructure electrocatalytic material is used to grow copper nanowires on the foam copper and synthesize molybdenum nitride and nickel cobalt nitride nanosheets on it to form molybdenum doped nickel cobalt The nanosheet covers the structure, and the conductivity and stability are improved through nitriding treatment.
It reduces material costs, improves hydrogen evolution performance with high current density, and maintains the stability of chemical composition and structure, which is significantly better than precious metal platinum wires.
Smart Images

Figure CN119433611A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy materials, and specifically relates to a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material and a preparation method and application thereof. Background Art
[0002] Currently, electrocatalytic hydrogen evolution reaction using clean electricity is considered the most promising technology for sustainable production. Alkaline water electrolysis is currently more attractive because it requires low-cost equipment and effectively avoids acid corrosion. In order to accelerate the slow kinetics caused by the additional water splitting step in alkaline electrolytes, efficient and highly stable catalysts are required, especially electrocatalytic materials that can withstand high current densities.
[0003] In the prior art, platinum-based catalysts are still the benchmark catalysts for hydrogen evolution reactions in acidic and alkaline electrolytes. However, platinum catalysts have the following technical problems: (1) High production cost: Platinum is a scarce and expensive metal, and its price fluctuations directly affect the manufacturing cost of fuel cells. As the demand for hydrogen fuel cells increases, the market demand for platinum continues to rise, and the supply may not be able to meet the demand, resulting in rising costs; (2) Catalyst stability: In fuel cells, platinum-based catalysts are prone to degradation of cell performance due to aggregation and dissolution of catalyst particles. Especially during long-term operation, these problems may cause battery performance to deteriorate; (3) Limited catalyst activity: Although platinum is an efficient catalyst, its activity may be affected by carbon carriers and other alloying elements in actual applications, which limits its further performance improvement.
[0004] There are many types of transition metals for hydrogen evolution catalysts, and transition metal nitrides usually have high catalytic activity. How to provide an element with abundant resources on Earth to replace precious metal platinum-based catalysts and design and develop HER catalysts that still maintain high stability at high current density is still a problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material and its preparation method and application in view of the deficiencies in the prior art. The electron transfer and heterostructure of molybdenum nitride and nickel cobalt nitride nanosheets are used to greatly reduce the internal resistance of the material and maintain the chemical composition and structural stability. Compared with the precious metal platinum wire, the composite electrocatalytic material not only greatly reduces the material cost, but also has a more excellent high current density hydrogen evolution performance.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention is to provide a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material, comprising the following steps:
[0008] S1, immersing the cut copper foam into dilute hydrochloric acid for pretreatment, and then rinsing and drying the copper foam, and then immersing the treated copper foam into a mixed solution of ammonium persulfate and sodium hydroxide to obtain copper hydroxide nanowires loaded on the copper foam;
[0009] S2, placing the copper hydroxide nanowire sample loaded on the copper foam obtained in step S1 in a muffle furnace for air calcination, and electrochemically reducing the calcined sample in a potassium bicarbonate electrolyte to obtain the copper nanowire loaded on the copper foam;
[0010] S3, placing the copper nanowires loaded on the copper foam obtained in step S2 in an electrolyte of nickel nitrate, cobalt nitrate and sodium molybdate, and loading the copper nanowires with molybdenum-doped nickel-cobalt nanosheets by electrochemical deposition;
[0011] S4, placing the copper nanowire-loaded molybdenum-doped nickel-cobalt nanosheets obtained in step S3 in a tubular furnace, and nitriding them in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel-cobalt nitride nanosheet heterostructure electrocatalytic material.
[0012] Furthermore, in step S1, the mass fraction of the dilute hydrochloric acid is 5wt% to 15wt%, and the molar ratio of the ammonium persulfate to the sodium hydroxide is (1 to 5): (10 to 20).
[0013] Furthermore, in step S2, the temperature of the muffle furnace is set to 100° C. to 200° C., and the air calcination time is 0.5 h to 2 h.
[0014] Furthermore, in step S2, the concentration of potassium bicarbonate is 0.1 mol / L to 1.5 mol / L, and the time of electrochemical reduction is 3000 to 6000 s.
[0015] Furthermore, in step S3, the molar ratio of the nickel nitrate, cobalt nitrate and sodium molybdate is (10-15):(10-15):(1-5).
[0016] Furthermore, in step S3, the electrochemical deposition time is 30 to 90 seconds.
[0017] Furthermore, in step S4, the temperature of the tube furnace is set to 100° C. to 500° C., and the calcination time is 1 h to 3 h.
[0018] The second aspect of the present invention is to provide a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material prepared by the above-mentioned preparation method.
[0019] The third aspect of the present invention is to provide the use of the above-mentioned molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material in electrolytic hydrogen production.
[0020] Furthermore, in a three-electrode system, a high current density electrocatalytic hydrogen evolution reaction was carried out using potassium hydroxide solution and sodium chloride solution as electrolytes.
[0021] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0022] (1) By growing copper nanowires on copper foam and synthesizing molybdenum nitride and nickel-cobalt nitride nanosheets on them, molybdenum-doped nickel-cobalt nanosheets are covered on the nanowires, effectively increasing the mass transfer and reaction area.
[0023] (2) The conductivity of molybdenum-doped nickel-cobalt nanosheets was greatly improved by nitriding. The incorporation of nitrogen can change the electronic structure and energy band structure, which helps the rapid transmission of electrons in the material and maintains the chemical composition and structural stability. At the same time, compared with precious metal platinum wire, the composite electrocatalytic material has better high current density hydrogen evolution performance.
[0024] (3) The preparation method provided by the present invention has the advantages of simple synthesis process, short synthesis cycle and low production cost. In addition, no hydrothermal reaction is required during preparation, and the preparation method has high safety and reliable repeatability, which is very suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of copper nanowires grown on the copper foam prepared in Example 1 of the present invention;
[0026] Figure 2 This is a scanning electron microscope photograph of molybdenum-doped nickel-cobalt nanosheets grown on copper nanowires prepared in Example 1 of the present invention;
[0027] Figure 3 The scanning electron microscope image and the transmission electron microscope image of the composite electrocatalyst material prepared in Example 1 of the present invention, (a) is a scanning electron microscope image, and (b) is a transmission electron microscope image;
[0028] Figure 4 This is an X-ray diffraction pattern of the composite electrocatalytic material prepared in Example 1 of the present invention;
[0029] Figure 5 This is a hydrogen evolution stability test curve diagram of this embodiment 1;
[0030] Figure 6a This is the X-ray photoelectron spectrum of the molybdenum element before and after the hydrogen evolution stability test of this embodiment 1;
[0031] Figure 6bThis is the X-ray photoelectron spectrum of nickel element before and after the hydrogen evolution stability test of this embodiment 1;
[0032] Figure 6c This is the X-ray photoelectron spectrum of the cobalt element before and after the hydrogen evolution stability test of this embodiment 1;
[0033] Figure 7 This is a comparison chart of the hydrogen evolution reaction activity of the composite electrocatalytic material prepared by Comparative Example 1, Comparative Example 2, and the noble metal platinum wire and Example 1 of the present invention;
[0034] Figure 8 This is a comparison chart of the hydrogen evolution reaction activity of the composite electrocatalytic materials prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0036] Example 1
[0037] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0038] The specific steps are as follows:
[0039] (1) Preparation of copper hydroxide nanowires loaded on copper foam: The cut copper foam was immersed in 15wt% dilute hydrochloric acid for pretreatment, and then washed and dried. The treated copper foam was immersed in a mixed solution of 0.1mol / L ammonium persulfate and 2mol / L sodium hydroxide to obtain copper hydroxide nanowires loaded on copper foam;
[0040] (2) preparing copper nanowires loaded on copper foam: placing the copper hydroxide nanowire sample loaded on copper foam obtained in step (1) in a muffle furnace and heating it to 180° C. at a rate of 4° C. / min, keeping the temperature for 2 hours, and electrochemically reducing the calcined sample in a 0.5 mol / L potassium bicarbonate electrolyte for 5000 s to obtain copper nanowires loaded on copper foam;
[0041] (3) Preparation of copper nanowires loaded with molybdenum-doped nickel-cobalt nanosheets: The copper nanowires loaded on copper foam obtained in step (2) are immersed in an electrolyte of 0.3 mol / L nickel nitrate, 0.3 mol / L cobalt nitrate and 0.05 mol / L sodium molybdate, and the copper nanowires are loaded with molybdenum-doped nickel-cobalt nanosheets by electrochemical deposition for 50 s. After washing and drying, the prepared catalyst is obtained.
[0042] (4) Preparation of molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material: Place the copper nanowires loaded with molybdenum-doped nickel cobalt nanosheets obtained in step (3) in a tubular furnace and heat the temperature to 400°C at a rate of 5°C / min, keep the temperature for 2 hours, and nitride in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0043] Example 2
[0044] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0045] The specific steps are basically the same as those in Example 1, except that the copper nanowire-loaded molybdenum-doped nickel-cobalt nanosheets obtained in step (3) are placed in a tubular furnace and heated to 300° C. at a rate of 5° C. / min, kept warm for 2 hours, and nitrided in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0046] Example 3
[0047] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0048] The specific steps are basically the same as those in Example 1, except that the copper nanowire-loaded molybdenum-doped nickel-cobalt nanosheets obtained in step (3) are placed in a tubular furnace and heated to 500° C. at a rate of 5° C. / min, kept warm for 2 hours, and nitrided in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0049] Example 4
[0050] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0051] The specific steps are basically the same as those in Example 1, except that the copper nanowire-loaded molybdenum-doped nickel-cobalt nanosheets obtained in step (3) are placed in a tubular furnace and heated to 600° C. at a rate of 5° C. / min, kept warm for 2 hours, and nitrided in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0052] Example 5
[0053] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0054] The specific steps are basically the same as those in Example 1, except that the copper nanowires loaded on the copper foam obtained in step (2) are immersed in an electrolyte of 0.3 mol / L nickel nitrate, 0.3 mol / L cobalt nitrate and 0.05 mol / L sodium molybdate, and the copper nanowires are loaded with molybdenum-doped nickel-cobalt nanosheets by electrochemical deposition for 100 s. After washing and drying, the prepared catalyst is obtained.
[0055] Example 6
[0056] This embodiment provides a method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material.
[0057] The specific steps are basically the same as those in Example 4, except that the copper nanowires loaded on the copper foam obtained in step (2) are immersed in an electrolyte of 0.3 mol / L nickel nitrate, 0.3 mol / L cobalt nitrate and 0.05 mol / L sodium molybdate, and the copper nanowires are loaded with molybdenum-doped nickel-cobalt nanosheets by electrochemical deposition for 30 s. After washing and drying, the prepared catalyst is obtained.
[0058] Comparative Example 1
[0059] (1) Preparation of copper hydroxide nanowires loaded on copper foam: The cut copper foam was immersed in 15wt% dilute hydrochloric acid for pretreatment, and then washed and dried. The treated copper foam was immersed in a mixed solution of 0.1mol / L ammonium persulfate and 2mol / L sodium hydroxide to obtain copper hydroxide nanowires loaded on copper foam;
[0060] (2) preparing copper nanowires loaded on copper foam: placing the copper hydroxide nanowire sample loaded on copper foam obtained in step (1) in a muffle furnace and heating it to 180° C. at a rate of 4° C. / min, keeping the temperature for 2 hours, and electrochemically reducing the calcined sample in a 0.5 mol / L potassium bicarbonate electrolyte for 5000 s to obtain copper nanowires loaded on copper foam;
[0061] (3) Preparation of copper nanowires loaded with molybdenum hydroxide nanosheets: The copper nanowires loaded with copper foam obtained in step (2) are immersed in an electrolyte of 0.6 mol / L sodium molybdate, and the copper nanowires are loaded with molybdenum hydroxide nanosheets by electrochemical deposition for 50 s. After washing and drying, the prepared catalyst is obtained.
[0062] (4) Preparation of molybdenum nitride nanosheet structure electrocatalytic material: The copper nanowire-loaded molybdenum hydroxide nanosheet obtained in step (3) is placed in a tubular furnace and heated to 400°C at a rate of 5°C / min, kept warm for 2 hours, and nitrided in an ammonia nitrogen atmosphere to obtain a molybdenum nitride nanosheet structure electrocatalytic material.
[0063] Comparative Example 2
[0064] (1) Preparation of copper hydroxide nanowires loaded on copper foam: The cut copper foam was immersed in 15wt% dilute hydrochloric acid for pretreatment, and then washed and dried. The treated copper foam was immersed in a mixed solution of 0.1mol / L ammonium persulfate and 2mol / L sodium hydroxide to obtain copper hydroxide nanowires loaded on copper foam;
[0065] (2) preparing copper nanowires loaded on copper foam: placing the copper hydroxide nanowire sample loaded on copper foam obtained in step (1) in a muffle furnace and heating it to 180° C. at a rate of 4° C. / min, keeping the temperature for 2 hours, and electrochemically reducing the calcined sample in a 0.5 mol / L potassium bicarbonate electrolyte for 5000 s to obtain copper nanowires loaded on copper foam;
[0066] (3) Preparation of copper nanowires loaded with nickel-cobalt nanosheets: The copper nanowires loaded on the copper foam obtained in step (2) are immersed in an electrolyte of 0.3 mol / L nickel nitrate and 0.3 mol / L cobalt nitrate, and the copper nanowires are loaded with nickel-cobalt nanosheets by electrochemical deposition for 50 s. After washing and drying, the prepared catalyst is obtained.
[0067] (4) Preparation of nickel cobalt nitride nanosheet structure electrocatalytic material: The copper nanowires loaded with molybdenum-doped nickel cobalt nanosheets obtained in step (3) are placed in a tubular furnace and heated to 400°C at a rate of 5°C / min, kept warm for 2 hours, and nitrided in an ammonia nitrogen atmosphere to obtain a nickel cobalt nitride nanosheet structure electrocatalytic material.
[0068] The molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic materials prepared in Examples 1 to 6 all have similar microscopic morphology, structure and catalytic performance, and Example 1 is used as an example for illustration:
[0069] refer to Figure 1 , is a scanning electron microscope image of copper nanowires grown on the foam copper prepared in Example 1. It can be seen from the image that the copper nanowires are arranged one by one.
[0070] refer to Figure 2 , is a scanning electron microscope photograph of the molybdenum-doped nickel-cobalt nanosheets grown on the copper nanowires prepared in Example 1. It can be seen from the figure that the nanowires are covered by the nanosheets, which will provide a larger active area and mass transfer.
[0071] refer to Figure 3 , which are scanning electron microscope images and transmission electron microscope images of the composite electrocatalyst material prepared in Example 1, the molybdenum nitride and nickel cobalt nitride nanosheets are evenly distributed, and the surface of the nitrided nanosheets has a granular feel, further increasing the catalytic active area.
[0072] refer to Figure 4, is the X-ray diffraction diagram of Example 1. It can be seen from the figure that the composite material has copper (111), (200), and (220) crystal planes. Since the foam copper is used as the substrate, the loading amount of molybdenum nitride and nickel cobalt nitride is low, and no diffraction peak is formed. In this catalyst, the improvement of hydrogen evolution performance is mainly due to the electron transfer between molybdenum nitride and nickel cobalt nitride and the mass transfer of the heterogeneous structure.
[0073] refer to Figure 5 , is a hydrogen evolution stability test curve of Example 1. It can be seen from the figure that the composite electrocatalyst material has a hydrogen evolution stability of 500 mA cm -2 The hydrogen evolution performance was stable for 100 hours under high current density, and there was no significant change in the polarization curve before and after the stability test. The catalyst has stable hydrogen evolution performance mainly because the introduction of nitrogen atoms can enhance the binding force between molybdenum, nickel and cobalt atoms, making the electrode material less likely to have atomic shedding, dissolution or migration, keeping the chemical composition and structure of the electrode surface stable, thereby maintaining stable hydrogen evolution performance.
[0074] refer to Figure 6a-6c , is the X-ray photoelectron spectrum of Example 1 before and after the hydrogen evolution stability test. It can be seen from the figure that there is no obvious change in the X-ray photoelectron spectrum of molybdenum, nickel, and cobalt elements before and after the stability test. The valence state of the elements of the composite electrocatalytic material did not change during the stability test, which is mainly due to the more stable structure of the nitride formed by the combination of molybdenum, nickel, cobalt and nitrogen atoms.
[0075] refer to Figure 7 , which is a comparison chart of the hydrogen evolution reaction activities of the composite electrocatalyst measured in the standard three-electrode system of Example 1, Comparative Example 1, Comparative Example 2 and the noble metal platinum wire. It can be found that the molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material prepared in Example 1 is significantly better than the single-component nitride electrocatalytic material in the high current density hydrogen evolution reaction, and shows a higher high current density hydrogen evolution performance than the noble metal platinum wire.
[0076] The molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material prepared in Examples 1-4 was tested for hydrogen evolution reaction activity. The results are as follows: Figure 8 As shown in the figure, a comparison of the hydrogen evolution reaction activities of the composite electrocatalysts measured under a standard three-electrode system is shown. It can be seen from the figure that the molybdenum nitride and nickel cobalt nitride nanosheets nitrided at different temperatures using this method can achieve relatively excellent performance, and the molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material prepared in Example 1 has the best high current density hydrogen evolution catalytic performance.
[0077] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material, characterized in that: The following steps are involved: S1, immersing the cut copper foam into dilute hydrochloric acid for pretreatment, and then rinsing and drying the copper foam, and then immersing the treated copper foam into a mixed solution of ammonium persulfate and sodium hydroxide to obtain copper hydroxide nanowires loaded on the copper foam; S2, placing the copper hydroxide nanowire sample loaded on the copper foam obtained in step S1 in a muffle furnace for air calcination, and electrochemically reducing the calcined sample in a potassium bicarbonate electrolyte to obtain the copper nanowire loaded on the copper foam; S3, placing the copper nanowires loaded on the copper foam obtained in step S2 in an electrolyte of nickel nitrate, cobalt nitrate and sodium molybdate, and loading the copper nanowires with molybdenum-doped nickel-cobalt nanosheets by electrochemical deposition; S4. Placing the copper nanowire-loaded molybdenum-doped nickel-cobalt nanosheets obtained in step S4 in a tubular furnace, and nitriding them in an ammonia nitrogen atmosphere to obtain a molybdenum nitride / nickel-cobalt nitride nanosheet heterostructure electrocatalytic material.
2. The preparation method according to claim 1, characterized in that In step S1, the mass fraction of the dilute hydrochloric acid is 5wt% to 15wt%, and the molar ratio of the ammonium persulfate to the sodium hydroxide is (1 to 5): (10 to 20).
3. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the muffle furnace is set to 100° C. to 200° C., and the air calcination time is 0.5 h to 2 h.
4. The preparation method according to claim 1, characterized in that: In step S2, the concentration of potassium bicarbonate is 0.1 mol / L to 1.5 mol / L, and the time of electrochemical reduction is 3000 to 6000 s.
5. The preparation method according to claim 2, characterized in that: In step S3, the molar ratio of nickel nitrate, cobalt nitrate and sodium molybdate is (10-15):(10-15):(1-5).
6. The preparation method according to claim 2, characterized in that: In step S3, the electrochemical deposition time is 30 to 90 seconds.
7. The preparation method according to claim 2, characterized in that: In step S4, the temperature of the tube furnace is set to 100° C. to 500° C., and the calcination time is 1 h to 3 h.
8. A molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material prepared by the preparation method as claimed in claims 1 to 7.
9. Use of the molybdenum nitride / nickel cobalt nitride nanosheet heterostructure electrocatalytic material as claimed in claim 8 in hydrogen production by electrolysis of water.
10. The use according to claim 9, characterized in that In a three-electrode system, potassium hydroxide solution and sodium chloride solution are used as electrolytes to carry out high current density electrocatalytic hydrogen evolution reaction.
Citation Information
Patent Citations
Copper nanowire loaded CoNi nanosheet electrocatalyst as well as preparation method and application thereof
CN113215617A
Preparation and application of copper nanowire loaded molybdenum oxide / molybdenum-nickel alloy core-shell material
CN115125577A
Foamed nickel loaded nickel nitride-molybdenum nitride catalyst as well as preparation method and application thereof
CN117779080A